2019
DOI: 10.3390/polym11101694
|View full text |Cite
|
Sign up to set email alerts
|

Employing of Trukhan Model to Estimate Ion Transport Parameters in PVA Based Solid Polymer Electrolyte

Abstract: In the current paper, ion transport parameters in poly (vinyl alcohol) (PVA) based solid polymer electrolyte were examined using Trukhan model successfully. The desired amount of lithium trifluoromethanesulfonate (LiCF3SO3) was dissolved in PVA host polymer to synthesis of solid polymer electrolytes (SPEs). Ion transport parameters such as mobility (μ), diffusion coefficient (D), and charge carrier number density (n) are investigated in detail using impedance spectroscopy. The data results from impedance plots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 91 publications
3
34
0
Order By: Relevance
“…Basically, it has been documented that the relaxation time increases as the ionic mobility decreases [57]. Specifically, the relaxation time decreases as conductivity increases, as reported in previous work [52,58,59,64]. In the current study, it was confirmed that the relaxation time increases when conductivity decreases.…”
Section: Study Of Dielectric Propertiessupporting
confidence: 87%
See 1 more Smart Citation
“…Basically, it has been documented that the relaxation time increases as the ionic mobility decreases [57]. Specifically, the relaxation time decreases as conductivity increases, as reported in previous work [52,58,59,64]. In the current study, it was confirmed that the relaxation time increases when conductivity decreases.…”
Section: Study Of Dielectric Propertiessupporting
confidence: 87%
“…More than one relaxation process causes the loss tangent peaks to be broad and to obey non-Debye type relaxation [57]. As previously shown, the tanδ plot is helpful in calculating transport parameters, namely the diffusion coefficient, carrier density and mobility [58]. Conductivity and relaxation dynamics are frequency dependent and are responsible for charged species motion and the induction of dipoles in the polymer electrolyte.…”
Section: Study Of Dielectric Propertiesmentioning
confidence: 99%
“…It is seen, as glycerol concentration is increased, the ε ′ increases. This is owing to the increase in the number of charge carriers causing greater polarization [ 27 , 71 , 72 , 73 ]. Based on these results, it is easy to manipulate the conductivity of polymer electrolytes using the dielectric constant.…”
Section: Resultsmentioning
confidence: 99%
“…The dielectric properties must be calculated in order to analyze the ionic conductivity of the polymer electrolyte. The amount of free mobile ions in the polymer electrolyte can be augmented for the improvement of the conductivity and this can be shown in dielectric spectra [ 88 , 89 ]. This helps in gaining comprehension about polymers as well as their ionic conductivity and crystallinity [ 90 ].…”
Section: Resultsmentioning
confidence: 99%